2018
DOI: 10.21468/scipost.report.674
|View full text |Cite
|
Sign up to set email alerts
|

Report on scipost_201810_00003v1

Abstract: In this paper the production cross-section pp → (γ, Z) → ν τντ γ+X in pp collisions at √ s = 13, 14, 33 T eV is presented. Furthermore, we estimate bounds at the 95% C.L. on the dipole moments of the τ-neutrino using integrated luminosity of L = 100, 500, 1000, 3000 f b −1 collected with the ATLAS detector at the LHC and we consider systematic uncertainties of δ sys = 0%, 5%, 10%. We found that the current and future LHC bounds are weaker than other experiments reported in the literature. However, it is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Snell and Theeuwes (2020) presented a naturalistic narrative text in both Dutch and English and found that higher frequency structures facilitated Dutch-English bilinguals' eye movement reading behavior in both languages. Differences for bilingual adults reading narrative passages in L1 vs. L2 have been found for syntactic structures such as gerunds, participial phrases, and relative clauses (De Groot, 2018). Among monolingual children, word position during expository text reading has been found to impact offline comprehension (de Leeuw et al, 2016).…”
Section: Eye-tracking Studies Of Cross-linguistic Influence In Text Processingmentioning
confidence: 99%
“…Snell and Theeuwes (2020) presented a naturalistic narrative text in both Dutch and English and found that higher frequency structures facilitated Dutch-English bilinguals' eye movement reading behavior in both languages. Differences for bilingual adults reading narrative passages in L1 vs. L2 have been found for syntactic structures such as gerunds, participial phrases, and relative clauses (De Groot, 2018). Among monolingual children, word position during expository text reading has been found to impact offline comprehension (de Leeuw et al, 2016).…”
Section: Eye-tracking Studies Of Cross-linguistic Influence In Text Processingmentioning
confidence: 99%